Tourism Extractivism in Tourist Corridors in the Triple Border (Misiones Province, Argentina) - Enriz, Noelia Maria (2025)
Large-scale tourism appears to be an unavoidable event in the Iguazu area, and it is growing permanently. Tourism is an activity that is promoted as being allied with the preservation of natural resources and a provider of employment opportunities which have a significant impact on territorial organisation. In this case, the structuring resource of the tourism proposal is the Iguazu Falls. This paper analyses the various paradoxes of promoting "green tourism" in the Iguazu area from a perspective focused on the role of Indigenous communities in the area. The paper focuses particularly on the debates surrounding green tourism in areas of traditional indigenous occupation. Methodologically, the research is supported on ethnographic records stemming from fieldwork and workshops with key tourism actors in the region, as well as sources produced for tourism promotion generated in the last three years in the town of Puerto Iguazu (Misiones, Argentina).